Ergonomic risk associated with repetitive movements in workers at a plant of industrial products - Álvarez Chaves, Rolando (2015)
Musculoskeletal Disorders (MsDs) are work-related injuries to the musculoskeletal system that arise as a result of the different conditions under which workers must perform their duties. These conditions represent a risk due to the inadequate planning in the design of the workplace and / or organization of the task. During the situation Health analysis at the beginning of 2014 at an industrial products which workers must perform their duties. These conditions represent Rica, it was determined that the highest incidence of MsDs for 2013 was presented in the packaging area of the company. For this reason it was decided to conduct an ergonomic evaluation of the working conditions in the area. Because of the characteristics of the tasks carried out during the work cycles, the Check List OCRA tool was chosen to assess the risks associated with repetitive movements of upper limbs. The study was conducted specifically in the packer’s positions of plant 1; area preliminarily met the necessary characteristics, due to time and tool requirements, to perform the study. Finally it was concluded that there was indeed a real risk for the occurrence of injury from workplace conditions, particularly by the position adopted during the tasks.